2000
DOI: 10.1073/pnas.220430297
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization and N-terminal domain proximity underlie the function of the molecular chaperone heat shock protein 90

Abstract: Heat shock protein (hsp)90 functions in a complex chaperoning pathway where its activity is modulated by ATP and by interaction with several co-chaperones. One co-chaperone, p23, binds selectively to the ATP-bound state of hsp90. However, the isolated ATP-binding domain of hsp90 does not bind p23. In an effort to identify the p23-binding domain, we have constructed a series of hsp90 deletion mutants fused with glutathione-S-transferase (GST). Full-length GST-hsp90 is able to bind p23, and also, to chaperone as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
122
4
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(140 citation statements)
references
References 50 publications
10
122
4
3
Order By: Relevance
“…The specificity of using NRL(M185V)-p23/ Hsp90h-CRL was confirmed using Hsp90h2.2(K107A)-CRL, Hsp90h2.2(K111A)-CRL, and Hsp90h2.2(K107AK111A)-CRL mutant fusion constructs. These mutations are analogous to the K111A mutation in chicken Hsp90a that reduces binding to geldanamycin (29). Figure 3A (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…The specificity of using NRL(M185V)-p23/ Hsp90h-CRL was confirmed using Hsp90h2.2(K107A)-CRL, Hsp90h2.2(K111A)-CRL, and Hsp90h2.2(K107AK111A)-CRL mutant fusion constructs. These mutations are analogous to the K111A mutation in chicken Hsp90a that reduces binding to geldanamycin (29). Figure 3A (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Experimentally, N-domain proximity and nucleotide binding correlate with p23 binding to Hsp90 (44). In addition, fluorescence emission spectra of pyrene-derivatized Hsp90 (21) and electron microscopy of antibody decorated Hsp90 (45) also suggested N-domain proximity in the presence of ATP.…”
Section: Discussionmentioning
confidence: 91%
“…The functional consequences of these changes are still largely unclear. One of the few functional correlations of these rearrangements is that binding of the cofactor p23 requires ATP bound to Hsp90 (28) and the dimeric form of the N-terminal domains (22,29).…”
Section: Discussionmentioning
confidence: 99%
“…Here, cross-linking data indicate that the N-terminal domains associate in the presence of AMP-PNP, which had been suggested previously based on electron microscopic data (26). This seems to be a prerequisite for the association of Hsp90 with the co-chaperone p23, which is known to occur after ATP-binding (27,28,29). In the studies of Weikl et al (22) and Prodromou et al (25), fragments of Hsp90 lacking C-terminal domains were found to be considerably less active than wild-type Hsp90.…”
Section: Hsp90mentioning
confidence: 99%